# MATH HELP

posted by .

Two functions g and h are defined as :
g:x--> 2x+3/x-4

h:x --> 1/x

Write expressions for :

a) hg(x)
b) g inverse 1(x)

• MATH HELP -

I noticed from the "related Questions" below that you have posted this same question several times.
One of the reasons that you have not received an answer could be that your expression is ambiguous.
Do you mean (2x+3)/(x-4) or do you mean it to be as you actually typed it.

Also your expression of hg(x) is not expressed in a standard form
you often see it as h∘g(x) or h(g(x))
It looks like you just want the two functions multiplied.
If you just wanted the multiplication, then
and then you would expand and simplify that.

Lastly I am not sure what you mean by
g inverse 1(x) , do you want the inverse of g(x)?
that would be written as g^-1 (x)

## Similar Questions

1. ### Algebra

The directions to a problem say "write two equivalent expressions for the opposite, or additive inverse, of each polynomial). What is an "additive inverse"?
2. ### MATH

Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x) b) g inverse 1(x)
3. ### MATH

Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x) b) g inverse 1(x)
4. ### MATH

Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x) b) g inverse 1(x)
5. ### MATH HELP

Two functions g and h are defined as : g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x)
6. ### math(functions)

Find the inverse of f for which f is defined as f:x-(2x minus 1)divided by (2x plus 1)